EVOLUTION OF LIFE DEFIES DARWIN - Rao, Y. V. Subba; Rao, Y. V. Ramana (International Journal of Research -GRANTHAALAYAH, 2023)
Origin of Life is critical to Evolution. Finally, with elimination of metaphysics from the Panspermia Origin of Life debate, the purely Darwin’s geocentric theory of evolution in its entirety collapsed. The present study provides a viable alternative consistent with Panspermia Origin of Life to Darwin’s Theory. The proposed theory is just reverse process of utilisation of stored information in the DNA in Panspermia Origin for evolution of all life forms including humans endowed with intricate and complex brain capable of cognition and consciousness wherein the most likely connection between biological and extra-terrestrial occurrences is solar disturbances and their particle emissions.